2020
DOI: 10.1089/cbr.2019.3070
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long Noncoding RNA HOTAIR Contributes to Progression in Hepatocellular Carcinoma by Sponging miR-217-5p

Abstract: Background: Hepatocellular carcinoma (HCC) is an aggressive primary hepatic cancer with high malignancy and poor prognosis. Long noncoding RNA HOTAIR has been classified as an oncogene to accelerate cell proliferation, migration, and invasion in many cancer types by interacting with the miRNA. Therefore, we assumed that HOTAIR might participate in HCC cell progression by interacting with miR-217-5p expression. Materials and Methods: The expression of HOTAIR and miR-217-5p in 35 HCC patients and HCC cells was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…HOTAIR acts as a "mesenchymal" gene positively regulated in TGFb-induced EMT and is epistatic with respect to the EMT-TF Snail by controlling its repressive function in the chromatin context (13). Consistently, this lncRNA promotes tumorigenesis and metastasis formation in different epithelial cancers, including HCC: its increased expression causes the acquisition of metastatic properties while its knockdown impairs migration, invasion ability, and EMT in carcinoma cells (4,9,10,38,39). Coherently, HOTAIR repression is required in the maintenance of the epithelial differentiated state (11).…”
Section: Discussionmentioning
confidence: 93%
“…HOTAIR acts as a "mesenchymal" gene positively regulated in TGFb-induced EMT and is epistatic with respect to the EMT-TF Snail by controlling its repressive function in the chromatin context (13). Consistently, this lncRNA promotes tumorigenesis and metastasis formation in different epithelial cancers, including HCC: its increased expression causes the acquisition of metastatic properties while its knockdown impairs migration, invasion ability, and EMT in carcinoma cells (4,9,10,38,39). Coherently, HOTAIR repression is required in the maintenance of the epithelial differentiated state (11).…”
Section: Discussionmentioning
confidence: 93%
“…Recent findings have also related HOTAIR interference to Trastuzumab resistance in GC, through the sponging of miR-3030 and consequent upregulation of ERBB4 [133], which is responsible for activating the PI3K/ATK signalling pathway [134]. Several HOTAIR-dependent interferences in miR pathways have also been described in glioma [123], HCC [135][136][137] prostate cancer [138,139] and squamous cell carcinomas [140][141][142][143].…”
Section: Lncrna's Interferencementioning
confidence: 97%
“…It contains 2158 nucleotides, and its expression level in cancer tissues is higher than in normal tissues [ 8 ]. Studies have found that it functions as a ceRNA in the occurrence and development of GC, breast cancer [ 75 ], lung cancer [ 76 ], liver cancer [ 77 ], and other tumors [ 78 , 79 , 80 ], and it is also related to drug resistance [ 81 ].…”
Section: Lncrnas As Cernas In Gcmentioning
confidence: 99%